Effects of Public Private Partnerships On Education Service Delivery in Uganda: A Comparative Analysis of Technical Efficiency of Secondary Schools in Mukono District - Kyagulanyi, Ronald; Tumwebaze, Jonathan (My University, 2019)
In many countries globally including Uganda, governments have partnered with the private actors to deliver education services traditionally delivered by the private sector. This paper explored whether secondary schools under Public Private Partnership (PPP) arrangement are more efficient in respect to pass rate and enrolment. The study adopting a comparative research design compared secondary schools under Public Private Partnership (PPP) arrangement and those schools which are not under PPP arrangement. The analysis was based on sample of 95 secondary schools randomly selected from Mukono district. The results show that Non-PPP schools were more efficient than secondary schools under PPP arrangement in respect to pass rates. However, in respect to enrolment, secondary school schools under PPP were found to be more efficient. This implies that PPP arrangement impacts school enrolment by increasing the number of supported students to join the private school but this does not translate into school performance. Thus, although government efforts to partner with private secondary schools increases student enrolment, it has implications on school efficiency in respect to pass rate. The study recommends that PPP arrangement between government and private sector schools need to be revised to reflect the realities of the schools with respect to enrolment and performance outcomes.
Keywords: Public Private Partnerships; Efficiency; Education; Secondary schools